EVALUATING THE EFFECTS OF TADALAFIL ON LOWER URINARY TRACT SYMPTOMS DUE TO BENIGN PROSTATIC HYPERPLASIA: A SYSTEMATIC REVIEW AND META-ANALYSIS - Nofrian, Rifki Adhi; Adriansjah, Ricky (Indonesian Urological Association, 2026)
Objective: This review aims to assess tadalafil's efficacy and safety in managing BPH-LUTS, providing insights for clinical practice. Material & Methods: A systematic search strategy was conducted across several electronic reference databases (PubMed, Google Scholar, Proquest, and Cochrane) and included articles published between 2014-2024. Duplicate publications, review articles, and incomplete articles were excluded. Results: Database search yielded 302 articles, which were systematically eliminated, leaving 10 relevant articles. A total of 1.645 patients were involved in the 10 included studies. Of the 10 included studies, 9 were single-center studies and 1 was a multi-center study. Of all the studies, 7 were randomized controlled trials, 2 were observational trials, and 1 was a cohort study. From the meta-analysis test, it was found that the increase in IPSS 12 weeks after therapy was no different when administering tadalafil and tamsulosin. Conclusion: In conclusion, tadalafil monotherapy demonstrates comparable efficacy to tamsulosin in treating LUTS/BPH, with its approval stemming from its effectiveness in managing ED. The IPSS score between tadalafil and tamsulosin is considered similar statistically. Studies suggest synergistic effects when combined with alpha-blockers, offering promise for patients with concurrent conditions. Safety findings support its utility across diverse populations. Keywords: BPH, LUTS, tadalafil.